2021
DOI: 10.5398/tasj.2021.44.3.273
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance of Male Line of Superior Tropical Rabbit

Abstract: New Zealand White rabbits (NN) are known as broiler rabbits that are well adapted to the Indonesian environment. HyLa rabbits are rabbits imported from China that were selected for high reproduction and growth rates. The increased productivity of NN rabbits was achieved by crossing to HyLa rabbits. This study was aimed to evaluate HyLa and NN rabbits' productivity and their reciprocal crosses to develop a broiler rabbit adaptive to tropical climate. Forty heads of does and 20 heads of bucks of HyLa rabbit, 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In experiments to study the productivity of rabbits of different genotypes from crossing Hyla rabbits of the New Zealand white breed, researchers found that the multiparity of rabbits that descended from Hyla males was 8.1 units, and crossed rabbits -8.5 units (Brahmantiyo et. al., 2021).…”
Section: Table 1 Significance Of the Main Selection Traits In Materna...mentioning
confidence: 99%
“…In experiments to study the productivity of rabbits of different genotypes from crossing Hyla rabbits of the New Zealand white breed, researchers found that the multiparity of rabbits that descended from Hyla males was 8.1 units, and crossed rabbits -8.5 units (Brahmantiyo et. al., 2021).…”
Section: Table 1 Significance Of the Main Selection Traits In Materna...mentioning
confidence: 99%
“…In comparison to other livestock, rabbits possess unique characteristics, including a short generation interval, high production potential, rapid growth rate, and most importantly substantial genetic diversity T Egyptian Journal of Veterinary Sciences https://ejvs.journals.ekb.eg/ among strains, relative to genetic variation within breeds [9,10]. Therefore, crossbreeding systems can be employed in rabbits to enhance production through the utilization of complementary breed effects, heterosis and the ability to compare the performance of different breeds and their crosses [11,12].…”
Section: Introductionmentioning
confidence: 99%